2021
DOI: 10.3390/cells10010137
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Profiling of Coding and Noncoding Genes in Human Dopamine Neuron Differentiation

Abstract: Dopaminergic (DA) neurons derived from human pluripotent stem cells (hPSCs) represent a renewable and available source of cells useful for understanding development, developing disease models, and stem-cell therapies for Parkinson’s disease (PD). To assess the utility of stem cell cultures as an in vitro model system of human DA neurogenesis, we performed high-throughput transcriptional profiling of ~20,000 ventral midbrain (VM)-patterned stem cells at different stages of maturation using droplet-based single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…We established VM organoids by adapting a commonly used protocol for the generation of forebrain organoids 27 with the addition of dual-SMAD inhibition combined with exposure to SHH, GSK3i, and FGF8 in the same temporal sequence used in 2D culture to promote neurogenic conversion of VM FP progenitors toward a DA neuron identity (Fig. 1a) 28,29 . We confirmed that in 3D cultures, this patterning regime also resulted in efficient neuralization and ventral midbrain differentiation as evaluated by expression of CNPY1, LMX1a, LMX1b, OTX1, CORIN, SHH, and FOXA2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We established VM organoids by adapting a commonly used protocol for the generation of forebrain organoids 27 with the addition of dual-SMAD inhibition combined with exposure to SHH, GSK3i, and FGF8 in the same temporal sequence used in 2D culture to promote neurogenic conversion of VM FP progenitors toward a DA neuron identity (Fig. 1a) 28,29 . We confirmed that in 3D cultures, this patterning regime also resulted in efficient neuralization and ventral midbrain differentiation as evaluated by expression of CNPY1, LMX1a, LMX1b, OTX1, CORIN, SHH, and FOXA2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5a). We also performed scRNAseq of one-month-old MLOs generated using the protocol described by Jo et al (29,112 cells analyzed from two replicates), which showed the presence of the same cell types at the same timepoints (Supplementary Fig. 5b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 20 years, the most widely used differentiation protocols have all been based on adherent 2D cellular cultures, and a variety of approaches driving stem cell commitment toward neuron differentiation are currently available [32,33]. Although a 2D configuration limits cell growth to a monolayer and is reductionist in nature, 2D cell culture has the great advantage of generating homogeneous populations of differentiated cells with high purity, and of enabling uniform accessibility to patterning factors and gas exchange [20,34].…”
Section: D Culturementioning
confidence: 99%
“…Dual SMAD inhibitors blocking TGFb and BMP signaling, combined with the ventralizing factor SHH and the caudalizing factor CHIR99021 for WNT pathway activation, are used for efficient specification of VM progenitors expressing a unique combination of markers found only in the midbrain floor plate, including FOXA2, LMX1A, EN1, and CORIN [17,41]. hPSC-derived DA progenitors can further differentiate into functional DA neurons with electrophysiological properties, and evidence indicates that they can also survive and mature after intracerebral transplantation in a rat model of PD, giving rise to DA-rich grafts that are able to innervate the host brain, leading to functional recovery [20,33].…”
Section: D Culturementioning
confidence: 99%